Optimalisasi Pelayanan Publik Dalam Penyelenggaraan Pemerintahan Daerah - Kencana, Marifa Ayu (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2005)
This article elucidates some ideas for Regional Governments to act changes in providing public service in order to recover their public trust. First, the governments public servants must understand and be commited to the vision and missions of their organisation. Second, the government must concentrate on its functions of regulating and delegate its functions of servicing, empowering, and regional developing to its community and etrepeneurs. Therefore, the governments must identify and take over which services cannot be provided by private organisations and fot that they must improve their public service management.